Sustainable fall prevention across Europe: challenges and opportunities - van der Velde, Nathalie; Seppala, Lotta; Petrovic, Mirko; Ryg, Jesper; Tan, Maw Pin *; Montero-Odasso, Manuel; Martin, Finbarr C; Masud, Tahir (Springer, 2022)
Falls and related injuries form a growing health-care problem in aging societies. Between 40 and 60% of older fallers in the last year report being injured [1]. Around 15–20% of falls result in serious (non-fracture) injuries including fractures [2]. Non-injurious falls have also been associated with adverse health effects, including accelerated functional decline, anxiety and depression, fear of falling, and social withdrawal [3]. Consequently, fall incidents have an impact on societal health-care expenditure, equaling 0.85–1.5% of the total health-care expenditure in Western countries [4].